Paweł Prüfer – Credibility and social relations Piotr Sztompka, "Wiarygodność. Sekret dobrych relacji", Znak Horyzont, Kraków 2023, ss. 318 - Paweł Prüfer (Studia z Teorii Wychowania)
The review (review essay) presents and analyzes the sociological discourse of Piotr Sztompka in relation to the category of credibility, lived, experienced and analyzed in society, especially in relational contexts. The author diagnoses the category of credibility in various areas of social life, including science, medicine and politics. This sociological argument is also open to formulating postulates that are educational and socializing in nature, and aimed at shaping a culture of credibility in theory and practice.